X-ray-induced conductivity in iron-doped lithium niobate crystals - Berben, D.; Sturman, B.; Freschi, A. A. [UNESP]; Buse, K. (American Physical Society (APS), 2003)
Illumination of photorefractive, iron-doped lithium niobate crystals (LiNbO 3:Fe) with x-rays generates a conductivity that we determine from the speed of hologram erasure. The doping levels of the crystals and the acceleration voltage of our x-ray tube are varied. A theoretical model is presented, which describes the obtained results. A decrease of the conductivity with increasing Fe 2+ concentration can be explained by assuming that holes are the dominant charge carriers for this short-wavelength illumination.
Keywords: iron derivative; lithium; niobium; oxygen derivative; concentration (parameters); conductance; crystal structure; holography; illumination; light refraction; theory; X ray analysis